Effects of amniotic fluid on human keratinocyte gene expression: Implications for wound healing. Issue 5 (15th January 2022) - Nyman, Erika; Lindholm, Elvira; Rakar, Jonathan; Junker, Johan P. E.; Kratz, Gunnar
Abstract: Cutaneous wounds can lead to huge suffering for patients. Early fetal wounds have the capacity to regenerate without scar formation. Amniotic fluid (AF), containing hyaluronic acid (HA), may contribute to this regenerative environment. We aimed to analyse changes in gene expression when human keratinocytes are exposed to AF or HA. Human keratinocytes were cultured to subconfluence, starved for 12 h and then randomised to be maintained in (1) Dulbecco's modified Eagle's medium (DMEM), (2) DMEM with 50% AF, or (3) DMEM with 50% fetal calf serum (FCS). Transcriptional changes were analysed using microarray and enriched with WebGestalt and Enrichr. Additionally, eight diagnostic genes were analysed using semiquantitative real‐time PCR to investigate epidermal differentiation and cellular stress after HA exposure as an alternative for AF exposure. The AF and FCS treatments resulted in enrichment of genes relating to varied aspects of epidermal and keratinocyte biology. In particular, p63‐, AP1‐ and NFE2L2‐ (Nrf2) associated genes were found significantly regulated in both treatments. More genes regulated by FCS treatment were associated with inflammatory signalling, whilst AF treatment was dominantly associated with molecular establishment of epidermis and lipid metabolic activity. HA exposure mostly resulted in gene regulation that was congruent with the AF microarray group, with increased expression of ITGA6 and LOR. We conclude that AF exposure enhances keratinocyte differentiation in vitro, which suggests that AF constituents can be beneficial for wound‐healing applications.